2010
DOI: 10.1007/s00540-010-0898-1
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil versus fentanyl compared in a target-controlled infusion of propofol anesthesia: quality of anesthesia and recovery profile

Abstract: We concluded that in propofol-based TCI anesthesia under BIS supervision for septorhinoplasty operations, remifentanil was better than fentanyl, especially with respect to emergence from total intravenous anesthesia (TIVA). Furthermore, the durations of anesthesia and operation were rather short, which indicates that fentanyl can be safely used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…When we separated the study protocols to enable a comparison of remifentanil use with the administration of alfentanil, fentanyl, or sufentanil, we found that remifentanil was associated with an increased incidence of postoperative shivering compared with alfentanil (RR = 2.73; 95% CI, 1.72-4.34; P b .0001; I 2 = 0.00%; Cochran's Q = 5.27) [1,2,11,[16][17][18][19][20][21][22][23][24][25][26][27][28]31,32] or fentanyl (RR = 2.04; 95% CI, 1.60-2.60; P b .00001; I 2 = 0.00%; Cochran's Q = 1.13) [3,10,12,19,30,33,34], but no significant difference was seen when compared with sufentanil (RR = 2.13; 95% CI, 0.67-6.74; P = .20; I 2 = 0.00%; Cochran's Q = 1.07) [17,18,29] as shown in Figure 2. The study protocol included the use of propofol or inhalation anesthesia for the maintenance of anesthesia.…”
Section: Results Of the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…When we separated the study protocols to enable a comparison of remifentanil use with the administration of alfentanil, fentanyl, or sufentanil, we found that remifentanil was associated with an increased incidence of postoperative shivering compared with alfentanil (RR = 2.73; 95% CI, 1.72-4.34; P b .0001; I 2 = 0.00%; Cochran's Q = 5.27) [1,2,11,[16][17][18][19][20][21][22][23][24][25][26][27][28]31,32] or fentanyl (RR = 2.04; 95% CI, 1.60-2.60; P b .00001; I 2 = 0.00%; Cochran's Q = 1.13) [3,10,12,19,30,33,34], but no significant difference was seen when compared with sufentanil (RR = 2.13; 95% CI, 0.67-6.74; P = .20; I 2 = 0.00%; Cochran's Q = 1.07) [17,18,29] as shown in Figure 2. The study protocol included the use of propofol or inhalation anesthesia for the maintenance of anesthesia.…”
Section: Results Of the Meta-analysismentioning
confidence: 99%
“…The meta-analysis by Komatsu et al included results contained in conference abstracts [14,15], and we were unable to acquire the results of 1 postoperative shivering trial [16]. In addition, papers that have been published since the meta-analysis by Komatsu et al showed no significant difference in the incidence of shivering when remifentanil was compared with fentanyl or sufentanil [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, remifentanil is preferable to fentanyl as an opioid during TIVA for surgery because of faster emergence from anesthesia, few postoperative side effects, and early discharge from hospital [10][11][12]. Coskun et al [13] reported that eye opening time, and extubation time for TIVA with remifentanil-propofol were significantly shorter than those for TIVA with fentanyl-propofol. These were similar to our results.…”
Section: Discussionmentioning
confidence: 98%
“…Coşkun et al used remifentanil and fentanyl as bolus injection for anesthesia induction in combination with propofol infusion and as infusion for maintenance. 15 In the remifentanil group, the spontaneous eye opening time, and extubation time was significantly shorter compared to the fentanyl group.…”
Section: Discussionmentioning
confidence: 86%